2016
DOI: 10.1002/pc.24014
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of resin crosslinking ratio on mechanical properties of epoxy‐based nanocomposites using molecular dynamics

Abstract: Finite-element method and micromechanical formulations have been used to predict mechanical properties of epoxy-based nanocomposites in recent years. The results of these investigations, however, show large scatters and do not agree well with experimental measurements. The differences in the results may be due to the fact that these approaches do not take some important material parameters into account, such as resin crosslinking ratio, nanotube/matrix interface, and nanotube agglomeration. The main objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 35 publications
(73 reference statements)
1
23
1
Order By: Relevance
“…The elastic properties of the interphase, however, are assumed to vary continuously between those of the main phases, that is, inclusion and matrix (Figs. [2][3][4][5][6]. Furthermore, inclusion is considered in cylindrical form.…”
Section: A Proposed Model For Characterizing Elastic Properties Of Thmentioning
confidence: 99%
See 1 more Smart Citation
“…The elastic properties of the interphase, however, are assumed to vary continuously between those of the main phases, that is, inclusion and matrix (Figs. [2][3][4][5][6]. Furthermore, inclusion is considered in cylindrical form.…”
Section: A Proposed Model For Characterizing Elastic Properties Of Thmentioning
confidence: 99%
“…For example, the transverse Young's modulus of the CNT‐reinforced epoxy‐based nanocomposites was found to be increased with the enhancement of resin's cross‐linking ratio. In addition, the CNT diameter was observed to have a strong influence on nanocomposite longitudinal and transverse moduli .…”
Section: Introductionmentioning
confidence: 97%
“…Note in this table that the effective fibers have transversely isotropic properties for all cases, as expected. In the above calculations, the matrix Young's modulus, E m , is assumed 2.8 GPa which is determined using molecular dynamics simulations .…”
Section: Multiscale Modelingmentioning
confidence: 99%
“…Due to the nano effect in nanostructured materials, nanocomposite mechanical properties are very sensitive to filler size . Nanocomposite mechanical properties are affected by different factors such as reinforcement size, distribution, orientation, and morphology . In CNT‐reinforced composites chirality and aspect ratio have great influences on elastic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the excellent specific strength, specific stiffness, thermal, electrical, and chemical properties of carbon nanotube (CNT) cause to use it as significant reinforcement materials for high performance structural composites with much application potential . Most studies on nanocomposite reinforced by CNT have focused on their material properties and some investigations have shown that the addition of small amount of CNT in the matrix can considerably improve the mechanical, electrical and thermal properties of polymeric composites . Martone et al studied on the effects of CNT aspect ratio (AR) and waviness on the reinforcement behavior of CNT/epoxy composite.…”
Section: Introductionmentioning
confidence: 99%